Electrochemical Corrosion Behavior of Titanium-Zirconium-Molybdenum Alloy. Issue 5 (May 2017) - Ping, Hu; Rui, Song; Kuaishe, Wang; Fan, Yang; Boliang, Hu; Zhen-yu, Chen; Qinwei, Li; Weicheng, Cao; Dongxin, Liu; Lei, Guo; Hailiang, Yu
Abstract: Titanium-zirconium-molybdenum (TZM) alloy and rare earth lanthanum doped La-TZM alloy were fabricated using powder metallurgy and rolling technique. Their electrochemical corrosion behavior was studied quantitatively using potentiodynamic polarization, scanning electron microscope and energy spectrum techniques. Their corrosion behavior was investigated in neutral, acidic and alkaline medium, while keeping the Cl − concentrations invariant. The results show that the corrosion resistance of the tested TZM alloy is better than that of the La-TZM alloy in neutral and alkaline media, while in an acidic medium, the La-TZM alloy is better. It is also found that the alloys are more corrosion-resistant in an acidic medium than in a neutral medium, and are the least corrosion-resistant in an alkaline medium. Finally, we find that Cl − effectively destroys the passivation film formed on the corrosion surface; OH − and Cl − double erosion promoted these two types of alloy intergranular corrosion increased.